Instruments of monetary-and-credit policy in terms of economic instability - Fedyshyn, Maiia (My University, 2020)
The article considers the problems of monetary-and-credit policy in the conditions of economic instability. The banking structure, with a detailed description of each component, is considered. Monetary-and-credit policy methods and instruments have been classified. The peculiarities of monetary regulation of the domestic economy in the context of transformation processes are characterized. The features and objectives of the monetary policy of the central bank are classified and described in detail. The use of reserve requirements in transition economies is considered. Revealed and substantiated the main threats to the monetary security of Ukraine. The factors limiting monetary policy are revealed. The substantiated need for modernization of available instruments of monetary policy of Ukraine in the conditions of market restrictions in the domestic and foreign markets and identified alternative instruments of influence on economic growth available to the NBU.
Keywords: Bank; Economic Instability; Instruments; Monetary-and-credit Policy